ANALYSIS OF DISTRIBUTION MANAGEMENT OF CAPTURE FISHERY PRODUCTS IN INCREASING FISHERMEN'S INCOME REVIEWED FROM AN ISLAMIC ECONOMIC PERSPECTIVE - Sarini Fitri Sarini; Kartubi; Hasmiza (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Indonesia ranks as the world's second-largest capture fisheries producer, yet approximately 90% of its fishers remain classified as small-scale operators with average incomes below the regional minimum wage across most coastal areas. This study aims to analyze capture fisheries distribution management limitations at the fisher level and examine their impact on small-scale fisher income welfare, evaluated through an Islamic economic perspective. A qualitative descriptive-analytical approach was employed, with data collected through in-depth interviews, participatory observation, and document analysis, validated through source triangulation. Findings reveal that distribution management is structurally constrained by intermediary dependency, cold chain infrastructure deficits, informational asymmetry, and debt-binding capital arrangements that collectively suppress fisher income at the point of first sale. Evaluated against Islamic economic principles of adl, tawazun, ta'awun, and kifayah, the existing distribution architecture constitutes a normatively unjust system in which productive value is disproportionately captured by downstream chain actors. These structural failures directly obstruct the achievement of SDG 1, SDG 8, SDG 10, and SDG 14. Institutional reform through cooperative strengthening, infrastructure investment, transparent price mechanisms, and sharia-compliant microfinance is prescribed as the foundational corrective toward a just and sustainable fisheries distribution system.